How is Telemedicine perceived? A qualitative study of perspectives from the UK and India - Chanda Rupa; Martínez Álvarez Melisa; Smith Richard D (BMC, 2011)
Abstract Background Improvements in communication and information technologies have allowed for the globalisation of health services, especially the provision of health services from other countries, such as the use of telemedicine. This has led countries to evaluate their position on whether and to what extent they should open their health systems to trade. This often takes place from the context of multi-lateral trade agreements (under the auspices of the World Trade Organisation), which is misplaced as a significant amount of trade takes place regionally or bi-laterally. We report here the results of a qualitative study assessing stakeholders' views on the potential for a bi-lateral trade relationship between India and the UK, where India acts as an exporter and the UK as an importer of telemedicine services. Methods 19 semi-structured interviews were carried out with stakeholders from India and the UK. The themes discussed include prospects on the viability of a bi-lateral relationship between the UK and India on telemedicine, current activities and operations, barriers, benefits and risks. Results The participants in general believed there were good prospects for telemedicine trade, and that this could bring benefits to "importing" countries in terms of cost-savings and faster delivery of care and to "exporting" countries in the form of foreign exchange and quality improvement. However, there were some concerns regarding quality of care, regulation, accreditation and data security. Conclusions There is potential for trade in this type of health services to succeed and bring about important benefits to the countries involved. However, issues around data security and accreditation need to be taken into consideration. Countries may wish to consider entering bi-lateral agreements, as they provide more potential to address the concerns and capitalise on the benefits. Finally, this paper concludes that more data should be collected, both on the volume of telemedicine trade and on the impact it is having on health systems, as currently there is very limited data on this.